Effects of light- vs. heavy-load squat training on velocity, strength, power, and total mechanical work in recreationally trained men and women - Valenzuela-Barrero, Carlos; Núñez-Sánchez, F. Javier; Loturco, Irineu; Pareja-Blanco, Fernando (Biology of Sport, 2024)
The purpose of this study was to investigate the effects of light and heavy loads in the squat exercise on kinematics and mechanical variables in recreationally trained men and women. Twenty-two men and sixteen women were assigned to 4 groups: 40% and 80% one-repetition maximum (1RM) male (M40 and M80) and female (F40 and F80). Over 6 weeks, participants performed twice a week the full back-squat (SQ) exercise with initially equated relative volume load (Sets*Repetitions/Set*%1RM). All groups performed different amounts of work ( p < 0.05), while relative work (work/1RM) only differed between load groups ( p 60%1RM; F40: 1.20 [0.52, 2.27]; F80: 2.20 [1.23, 3.93]; M40: 0.85 [0.29, 1.59]; M80: 1.03 [0.55, 1.77]), as well as small to moderate improvements in the average velocity against light loads (< 60%1RM; F40: 0.49[-0.24, 1.68]; F80: 1.10 [0.06, 3.16]; M40: 0.80 [0.41, 1.35]; M80: 0.93 [0.25, 1.84]). Lastly, only the F40 group showed small improvements in countermovement jump (CMJ) height (ES = 0.65 [0.14, 1.37]). In conclusion, light and heavy loads produced similar strength gains in men and women when initially equated by relative volume load, although the standardized mean differences suggest nuances depending on the sample and task.